IMPLEMENTASI KODE ETIK GURU DALAM KONTEKS PENDIDIKAN INKLUSI: STUDY KASUS DI SDN TIMURAN-PRAWIROTAN - Isa Abel Manik, Royda; Sanu Sabila, Eghes; Absti Cinta Fatiha, Hasna; Sufyan Chanif, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The implementation of teacher ethics in inclusive education requires professional, empathetic, and adaptive attitudes when assisting students who experience learning difficulties. The purpose of this study is to describe how the teacher’s code of ethics is applied at SD Negeri Timuran – Prawirotaman through direct observation of a student with writing difficulties (dysgraphia). The focus of the analysis includes the student’s profile, the type of learning difficulty, its causal factors, and the implementation of inclusive education in the school. The findings indicate that teachers strive to apply the principles of fairness, responsibility, and care by adjusting instructional methods, although they still face challenges related to limited resources, such as the absence of special education support teachers. These results emphasize that the application of teacher ethics in inclusive educational settings requires systemic support, collaboration with parents, and comprehensive assessment to ensure that educational services can be delivered optimally.